Cost-effectiveness of de-escalation from micafungin versus escalation from fluconazole for invasive candidiasis in China. (4th March 2018) - Chen, Dechang; Wan, Xianyao; Kruger, Eliza; Chen, Can; Yue, Xiaomeng; Wang, Liang; Wu, Jiuhong
Abstract: Aims: Guidelines on treating invasive candidiasis recommend initial treatment with a broad-spectrum echinocandin (e.g. micafungin), then switching to fluconazole if isolates prove sensitive (de-escalation strategy). This study aimed to evaluate the cost-effectiveness of de-escalation from micafungin vs escalation from fluconazole from a Chinese public payers perspective. Materials and methods: Cost-effectiveness was estimated using a decision analytic model, in which patients begin treatment with fluconazole 400 mg/day (escalation) or micafungin 100 mg/day (de-escalation). From Day 3, when susceptibility results are available, patients are treated with either fluconazole (if isolates are fluconazole-sensitive/dose-dependent) or micafungin (if isolates are resistant). The total duration of (appropriate) treatment is 14 days. Model inputs are early (Day 3) and end-of-treatment mortality rates, treatment success rates, and health resource utilization. Model outputs are costs of health resource utilization over 42 days, incremental cost per life-year, and incremental cost per quality-adjusted life-year (QALY) over a lifetime horizon. Results: In the base-case analysis, the de-escalation strategy was associated with longer survival and higher treatment success rates compared with escalation, at a lower overall cost (–¥1, 154; –175 United States Dollars). Life-years and QALYs were also better with de-escalation. Thus, this strategy dominated the escalation strategy for all outcomes. In a probabilistic sensitivity analysis, 99% of 10, 000 simulations were below the very cost-effective threshold (1 × gross domestic product). Limitations: The main limitation of the study was the lack of real-world input data for clinical outcomes on treatment with micafungin in China; data from other countries were included in the model. Conclusion: A de-escalation strategy is cost-saving from the Chinese public health payer perspective compared with escalation. It improves outcomes and reduces costs to the health system by reducing hospitalization, due to an increase in the proportion of patients receiving appropriate treatment.